الجديد في تحديد مسؤولية الناقل البحري بموجب قواعد روتردام دراسة مقارنة مع الاتفاقيات الدولية السابقة - يونس, الحسن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
قواعد روتردام هي ثمرة جهد دولي مكثف لإيجاد صك دولي يتلاءم مع ما أفرزته التطورات الحديثة في صناعة وتجارة النقل البحري ولذلك كان لا بد من تسليط الضوء على جزء اساسي من هذه القواعد هو التحديد القانوني لمسؤولية الناقل باعتباره العنصر الأساس في التعويض الذي سيتقاضاه الشاحن ووضع الأكاديمي والباحث والمختص بالشأن البحري أمام المفاهيم والتطورات الجديدة التي أدخلتها الاتفاقية و أسلوبها الحديث في التصدي لمشكلات النقل متعدد الوسائط وما ينطوي عليها من تنازع و اختلاف في حدود المسؤولية وفقاً للأنظمة القانونية المختلفة بما يمكن من تحديد دور هذه القواعد لدى بلورة موقف وطني بالانضمام أو العزوف عن هذه الاتفاقية. Rotterdam Rules is the result of an intensive international effort to find an international instrument in line with what was produced by recent developments in the maritime transport industry and trade . therefore ,it was necessary to highlight the essential part of these rules "legal limitation of the carrier liability" as a basic element in the compensation paid to shipper and put academic, researcher and specialist in maritime affairs in front of the new concepts and developments introduced by the convention and modern style in addressing the problems of multimodal transport including conflict and differences within the limits of liability in accordance with the different legal systems , so these rules can determine the national decision to join or refrain from this Convention.